Interaction Course of General and Professional-Pedagogic Education Training in Teaching Plans of Primary School Teacher Training Institutions 1918-1940 - Žemgulienė, Aušra (Acta Paedagogica Vilnensia, 2000)
The article reveals changes in the proportion of general and professional-pedagogical training of primary school teachers in Lithuania in 1918-1940. Teaching plans of teachers seminaries of 1919, 1922 and 1929 approved by Lithuanian Education Ministry were used to ascertain the ratio, alongside with data from „Teachers Seminary Project" proposed by Tauragė Teachers Seminary in 1927. Evident turn to teachers training pedagogization reflected in the afore mentioned project is close to teachers institute conception and the latest 1939 year teaching plan of Pedagogical Institute.
Keywords: Teachers' Seminary; teacher training; education.